A Systematic Literature Review of Recent Blockchain Platforms - Alrumaih, Malak Sulaiman; Hassan, Mohammad Mahdi; Martuza, Muhammad Ali; Alsuhibany, Suliman Abdallah (Journal of engineering sciences and information technology, 2024)
Blockchain is an emerging technology based on the digital ledger in the distributed system. The decentralized trust is one of its prominent features that ensures better transparency. Blockchain-based systems also enhance data integrity, confidentiality, and anonymity by eliminating third-party involvement in completing the transactions. Many SLRs have been published related to blockchain recently, but no comprehensive and systematic study on blockchain platforms has been conducted. So, there is a need for an organized and systematic review of blockchain platforms. This paper has reported a systematic literature review on existing blockchain platforms. We have formulated two research questions to determine the major frameworks used to implement blockchain-based systems and how they differ in implementation and operation. We have identified eighty-five blockchain platforms. To provide‎‎ comprehensive insights on blockchain platforms, we ‎identified related technologies and provided a map for ‎further ‎research development on blockchain technology.‎
Keywords: blockchain; platforms; distributed ledger; privacy and security; data ‎management; systematic literature review